Exploring Memorization Patterns in the Tahfidz and Tarjamah Qur'an Programs - Ermis Suryana; Udin Supriadi; Miftahul Fikri; Arvin Efriani; Sukree Langputeh (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
The memorization and understanding of the Qur'an play a vital role in shaping a Qur'anic generation. This study aims to explore the memorization patterns in the Tahfidz and Tarjamah Qur'an programs at Darul Hufadz Islamic Senior High School. Using a qualitative research approach, data were gathered through in-depth interviews, participatory observation, and documentation from 38 informants, including the principal, five mentor teachers, and 32 students. Data analysis followed a process of reduction, presentation, and verification. The findings indicate that the Tahfidzul Qur'an program follows a daily memorization pattern known as